Implementasi Pembentukan Karakter Siswa Di Mtsn 3 Pamekasan - Megawati Fajrin (AL -ALLAM, 2025)
This research is motivated by the researcher's interest in the efforts to build student character implemented at MTsN 3 Pamekasan. As the modern era develops, many cases occur and befall teenagers and students who violate community norms or rules in the environment and at Madrasah and this can be disturbing for parents, teachers, and the community. And it is necessary for the process or program to build student character so that more or less children can anticipate and even minimize actions that violate these rules and norms. In this case, character education needs to be applied to students, so that the character can contribute greatly in realizing the full potential and ideals of a person in building a good and beneficial life for themselves and others. Methodologically, this research uses a qualitative approach with a phenomenological type of research. The data collection techniques for this research include: observation, interviews and documentation through media, archival records. Test the validity of the data through careful re-checking and extending the research time, perseverance, observation, triangulation. The results of this study indicate that: First; the habit of exemplary behavior carried out in madrasas such as shaking hands with teachers of the same sex, reciting the Koran and praying together before the teaching and learning process begins, congregational prayers in each class alternately, the implementation of the SKIM book (Syarat Kecakapan Ibadah Mahdhoh), the Sakusiswa book as a form of student discipline and Friday afternoon preaching. Second; the results of the formation of good and excellent student character can be seen from the student achievements obtained and changes in student behavior and good deeds as well. Third; The supporting factors are providing role models, references, or student books, madrasa facilities and infrastructure and the community being a supporter of the formation of student character, complete facilities including fences if children are late coming to the madrasa, good cooperation between BK teachers, discipline enforcers, and the sincerity of teachers to educate and improve student behavior, and the holding of extracurricular activities such as scouts and pancake silat. The inhibiting factors in this study were caused by the community due to behavior carried out by the community such as falling into the realm of drugs, the limitations of the madrasa in reaching information, the very varied geographical location of students, the limitations of parents regarding the rules and regulations of the madrasa, and the lack of parental attention.